Lymphangiomatous Polyp Presenting as Tonsillar Mass - Ashish Dhakal; Sameer Karmacharya; Sandhya Shrestha (Case Reports in Otolaryngology)
A 19-year-old female presented to ENT OPD of Dhulikhel Hospital, Kathmandu University Hospital, with history of foreign body sensation in throat for 2 weeks and mass in left tonsil for 1 week. There is no history of difficulty swallowing or recurrent throat infection. Physical examination revealed a pedunculated mass arising from upper pole of left tonsil. Bilateral tonsillectomy was done under general anaesthesia. Grossly, 2.5 × 1.5 × 1 cm polypoidal mass, soft in consistency, was found to be attached to left tonsil. Histopathology report was consistent with lymphangiomatous polyp of tonsil. Postoperative period was uneventful and she was normal during her follow-up at 1 month with bilateral healthy tonsillar fossa.